Spatial and Temporal Analysis of Gallbladder Stone Cases at dr. Soekardjo Hospital, West Java: An Evidence-Based Study - Mudatsir Mudatsir; Muhammad Raka El Ghifari; Fahmi Rahmat Amanulloh; Tryantini Sundi Putri; Andhy Romdani (Medica Hospitalia : Journal of Clinical Medicine, 2025)
BACKGROUND: Gallbladder stone cases in East Priangan area have significantly increased due to diet, lifestyle, and stress levels of the community. However, studies on the seasonal variation of gallbladder stone cases remains limited, particularly in Indonesia. AIMS: This study aims to investigate the occurrence of gallbladder stone cases in East Priangan, West Java, Indonesia, based on the medical reports in 2022−2023. Furthermore, the dispersal of gallbladder stone cases is mapped as spatial and temporal distributions. METHOD: This study employed an observational, cross-sectional design. Data was collected from the medical records at dr. Soekardjo General Hospital of Tasikmalaya between January 2022 and December 2023. Data used in this study were available data of 2,032 visit records, comprising 1,311 visits in 2022 and 991 visits in 2023, for both inpatient and outpatient care. Two types of statistical tests were used in this study: the Chi-Square test and Moran's I value. RESULT:  The Global Moran’s I test revealed clusters in the spatial distribution of gallbladder stone for both 2022 (I = 0.434) and 2023 (I = 0.521). Additionally, monthly variations (p = 0.001), age (p = 0.023), and gender (p = 0.001) were found to be statistically significant factors influencing the risk of gallbladder stones. CONCLUSION: The spatial distribution of gallbladder stone was concentrated in the certain clusters. Moreover, there were significant correlations between monthly variations, age, and gender with gallbladder stones.